Do the physiotherapy results make us happy in a case with 'happy puppet' (Angelman) syndrome?. (29th December 2010) - Kara, Ozgun Kaya; Mutlu, Akmer; Gunel, Mintaze Kerem; Haliloglu, Goknur
Abstract : This study aimed to investigate the benefits of physiotherapy programme in a patient with Angelman syndrome (AS) during a follow-up of 3 years. Assessments included: disability level with gross motor function classification systems, gross motor function with gross motor function measurement (GMFM), balance with Berg Balance Scale, motor performance with gross motor performance measurement (GMPM) and tonus assessment with Modified Ashworth Scale. Physiotherapy programme was performed during 36 months, 3 days per week by physical therapist according to Neurodevelopmental Treatment approach. During the 36 months, GMFM increased from 11.46% to 70.82% and GMPM increased from 1.25% to 70.25%. This case report is the first study about the effectiveness of physiotherapy with medium-term follow-up in a child with AS. Physiotherapy results make us happy in this particular patient with 'happy puppet' syndrome.